Fluorescent Triazole Urea Activity‐Based Probes for the Single‐Cell Phenotypic Characterization of Staphylococcus aureus - Chen, Linhai; Keller, Laura J.; Cordasco, Edward; Bogyo, Matthew; Lentz, Christian S. (Angewandte Chemie International Edition, 2019)
Phenotypically distinct cellular (sub)populations are clinically relevant for the virulence and antibiotic resistance of a bacterial pathogen, but functionally different cells are usually indistinguishable from each other. Herein, we introduce fluorescent activity‐based probes as chemical tools for the single‐cell phenotypic characterization of enzyme activity levels in Staphylococcus aureus. We screened a 1,2,3‐triazole urea library to identify selective inhibitors of fluorophosphonate‐binding serine hydrolases and lipases in S. aureus and synthesized target‐selective activity‐based probes. Molecular imaging and activity‐based protein profiling studies with these probes revealed a dynamic network within this enzyme family involving compensatory regulation of specific family members and exposed single‐cell phenotypic heterogeneity. We propose the labeling of enzymatic activities by chemical probes as a generalizable method for the phenotyping of bacterial cells at the population and single‐cell level. A different (pheno)type of probe: A toolkit of clickable and fluorescent activity‐based triazole urea probes enables the selective manipulation and visualization of different serine hydrolases in live S. aureus cells. These probes were used to dissect phenotypic differences among bacterial cells at the population and single‐cell level.